Efek Seed Priming KNO3 terhadap Perkecambahan dan Pertumbuhan Awal Benih Padi Varietas IR 64 pada Beberapa Tingkat Salinitas - Puji Ramadhani; Annisa Mardhatillah; Violita Violita (Universitas Cokroaminoto Palopo, 2026)
Salinity is one of the major limiting factors in rice cultivation, negatively affecting seed germination and early plant growth. One approach that can be taken to improve seed tolerance under saline conditions is seed priming. This study aims to examine the effect of potassium nitrate (KNO3) seed priming on the germination and early growth of IR 64 rice seeds at various salinity levels. This study was an experiment designed using a completely randomized design with a single treatment factor, namely NaCl salinity levels (0, 50, 100, and 150 mM), in which all seeds were treated with 1% KNO3 seed priming prior to stress application. Each treatment was replicated four times. The observed parameters included germination percentage, root length, shoot length, seedling length, and seed vigor index. The data were analyzed using analysis of variance (ANOVA) followed by Duncan’s multiple range test at a 5% significance level. The results showed that KNO3 seed priming was able to maintain the germination percentage of IR 64 seeds at all salinity levels, with values that were not statistically significantly different. However, increasing NaCl concentrations had a significant negative effect on the morphological growth of seedlings, as indicated by a decrease in root length, shoot length, seedling length, and seed vigor index. The treatment without salinity produced the best early growth, while high salinity significantly inhibited seedling growth. Based on these results, it can be concluded that KNO3 seed priming plays an effective role in maintaining the viability of IR 64 rice seeds under saline conditions, but it is not yet fully capable of overcoming the negative effects of salinity on early plant growth.